Answers

2015-05-17T09:48:35+05:30
 b^{2} x^{2} + a^{2} y^{2} , in this equation we substitute the x and y values
hence it becomes b^{2} (a cos \theta )^{2} + a^{2} ( ysin \theta )^{2} 
⇒ b^{2} a ^{2} cos^{2} \theta + a ^{2} b^{2} sin^{2} \theta 
⇒ a^{2} b^{2} cos^{2} \theta + a^{2} b^{2} sin^{2} \theta 
⇒a ^{2} b^{2} ( cos^{2} \theta +sin^{2} \theta )
⇒ a^{2} b^{2}      (as sin^{2} \theta + cos^{2} \theta=1 )
0
2015-05-21T22:14:00+05:30
 b^{2} x^{2} + a^{2} y^{2} , in this equation we substitute the x and y values
hence it becomes b^{2} (a cos \theta )^{2} + a^{2} ( ysin \theta )^{2} 
⇒ b^{2} a ^{2} cos^{2} \theta + a ^{2} b^{2} sin^{2} \theta 
⇒ a^{2} b^{2} cos^{2} \theta + a^{2} b^{2} sin^{2} \theta 
⇒a ^{2} b^{2} ( cos^{2} \theta +sin^{2} \theta )
⇒ a^{2} b^{2}      (as sin^{2} \theta + cos^{2} \theta=1 )
0